Differential Effects of Acute (Extenuating) and Chronic (Training) Exercise on Inflammation and Oxidative Stress Status in an Animal Model of Type 2 Diabetes Mellitus - Edite Teixeira de Lemos; Rui Pinto; Jorge Oliveira; Patrícia Garrido; José Sereno; Filipa Mascarenhas-Melo; João Páscoa-Pinheiro; Frederico Teixeira; Flávio Reis (Hindawi Limited, 2011)
This study compares the effects of a single bout of exercise (acute extenuating) with those promoted by an exercise training program (chronic), focusing on low-grade chronic inflammation profile and on oxidative stress status, using the obese ZDF rats as a model of type 2 diabetes mellitus (T2DM). Animals were sacrificed after 12 weeks of a swimming training program and after a single bout of acute extenuating exercise. Glycaemic, insulinemic, and lipidic profile (triglycerides, total-cholesterol) were evaluated, as well as inflammatory (serum CRPhs, TNF-α, adiponectin) and oxidative (lipidic peroxidation and uric acid) status. When compared to obese diabetic sedentary rats, the animals submitted to acute exercise presented significantly lower values of glycaemia and insulinaemia, with inflammatory profile and oxidative stress significantly aggravated. The trained animals showed amelioration of glycaemic and lipidic dysmetabolism, accompanied by remarkable reduction of inflammatory and oxidative markers. In conclusion, the results presented herein suggessted that exercise pathogenesis-oriented interventions should not exacerbate underlying inflammatory stress associated with T2DM.